VIETNAM: POTENTIAL MARKET FOR ATTRACTING FOREIGN DIRECT INVESTMENT AFTER THE COVID-19 PANDEMIC - Loc, Tran My Hai (The journal of contemporary issues in business and government, 2021)
The COVID-19 pandemic, which has had a broad and deep influence on all countries, is currently unfolding in a complex manner. The world economy has entered a deep recession. Vietnam, a country with a high level of economic openness and substantial international connectivity, has also been hit by the COVID-19 outbreak. Vietnam's economy, on the other hand, has maintained its development, with an anticipated GDP growth rate of 2,91 percent. Following the COVID-19 pandemic, Vietnam is progressively becoming a promising market for attracting foreign direct investment due to key socioeconomic policies and goals, as well as the country's remarkable advantages and position in the international arena.